Analysis of the Utilization of Artificial Intelligence (AI) as a Source of Learning Media for Islamic Religious Education - Susanti, Eva; Amin, Alfauan (Universitas Muhammadiyah Makassar, 2025)
Artificial Intelligence (AI), also known as artificial intelligence, is a computer system-based technology that allows humans to perform activities that require human intelligence. AI has penetrated into the world of education which makes AI quite potential to help education. The purpose of this research is to analyze the use of AI as a source of learning media that can be used in PAI learning. The research method used in this research is the library research method with books, journals and web articles about AI, learning resources, learning media and PAI as a source of information. The result of this research is that there are many AI derivatives or programs that can be used by PAI teachers as a source of learning media to help the learning process become more effective, including canva, ChatGPT, Skype, and many more.